A new approach to estimate fecundity rate from inter‐birth intervals. Issue 4 (18th April 2017) - Arso Civil, Mònica; Cheney, Barbara; Quick, Nicola J.; Thompson, Paul M.; Hammond, Philip S.
Abstract: Accurate estimates of fecundity rate are key to population assessments and effectively direct conservation efforts. We present a new approach to estimate fecundity rate based on the probability of a female giving birth, conditional on a previous birth t years ago, from which an expected inter‐birth interval (IBI) can be estimated. We use generalized linear mixed‐effects models to account for individual and temporal variability and apply the approach to individual reproductive histories of bottlenose dolphins ( Tursiops truncatus ) from the east coast of Scotland. We estimate a fecundity rate of 0.222 (95% CI = 0.218–0.253) and an expected IBI of 4.49 yr (95% CI = 3.94–4.93 yr). We use simulated data samples to show that the approach produces estimates with a minimum bias of <3%. Simulations are also used to investigate the effect of the most common data‐driven biases in the estimates of birth intervals and fecundity rate; we recommend longitudinal studies of at least 10 yr and capture probabilities of at least 0.3 when using this methodology. The approach may be modified to incorporate other parameters of interest and should be applicable to any population with comprehensive data on birth intervals.